2014
DOI: 10.1002/adma.201305638
|View full text |Cite
|
Sign up to set email alerts
|

Tin Phosphide as a Promising Anode Material for Na‐Ion Batteries

Abstract: Sn4 P3 is introduced for the first time as an anode material for Na-ion batteries. Sn4 P3 delivers a high reversible capacity of 718 mA h g(-1), and shows very stable cycle performance with negligible capa-city fading over 100 cycles, which is attributed to the confinement effect of Sn nanocrystallites in the amorphous phosphorus matrix during cycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
298
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(312 citation statements)
references
References 31 publications
12
298
2
Order By: Relevance
“…This poor cyclability originates from the volume expansion during sodiation, the aggregation during desodiation, and the resulting deterioration of active material layer. 5 In contrast, the Sn 4 P 3 and SnP 3 electrodes showed an improved cyclability. In particular, the Sn 4 P 3 electrode exhibited a better performance: the capacities over 400 mA h g ¹1 was maintained until the 25th cycle.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This poor cyclability originates from the volume expansion during sodiation, the aggregation during desodiation, and the resulting deterioration of active material layer. 5 In contrast, the Sn 4 P 3 and SnP 3 electrodes showed an improved cyclability. In particular, the Sn 4 P 3 electrode exhibited a better performance: the capacities over 400 mA h g ¹1 was maintained until the 25th cycle.…”
Section: Resultsmentioning
confidence: 96%
“…[4][5][6] It has been recently reported that Sn 4 P 3 showed a synergistic Na-storage reaction where Sn and P atoms can react with Na to form Na 15 Sn 4 and Na 3 P, and that the resulting Na 15 Sn 4 alloy acts as a conducting pathway to activate the reversible Na-storage reaction of nonconductive Na 3 P particles while the well-dispersed Na 3 P phase provides a shield matrix to prevent the aggregation of the Na 15 Sn 4 / Sn nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…High volumetric and gravimetric energy density and reasonably high capacity makes tin phosphides promising anode materials [156]. A stable capacity of up to 600-720 mAh g −1 can be sustained during 100 cycles at 100 mA g −1 current density for ball-milled samples of Sn 4 P 3 ( Figure 18(b)) [177,178]. To improve cycling stability, several approached have been applied, such as modifying electrolyte [179] and synthesizing nanocomposites with various forms of carbon or reduced graphene oxide [175,176,180].…”
Section: Tetrel (Si Ge Sn) Phosphidesmentioning
confidence: 99%
“…Sodium stannide is a conductive metallic material while sodium phosphide is a semiconductor. A nanocomposite of Na 15 Sn 4 and Na 3 P exhibits high conductivity and no particles aggregation and phase separation, which provides high stability upon electrochemical cycling [177][178][179][180]182].…”
Section: Tetrel (Si Ge Sn) Phosphidesmentioning
confidence: 99%
“…In this regard, metals, their sulfides, oxides, phosphides and alloys bring very interesting performances 25, 116, 117, 118, 119, 120, 121. But these performances are also accompanied by new fundamental issues related to their structural change, volume expansion, uncontrolled SEI film formation, and low conductivity that results in poor cyclic life 21, 37, 97, 122, 123, 124.…”
Section: Advanced Electrode Nanostructures For Lithium‐based Batteriesmentioning
confidence: 99%